Creating New Pasts: Reality, Facticity and Interpretation in Peirce and Heidegger - Susanne Rohr (European Journal of American Studies)
Only recently have the striking parallels between Charles S. Peirce’s pragmatism and Martin Heidegger’s hermeneutics of facticity been fully acknowledged and assessed–the profound differences that, of course, exist between them, notwithstanding. This essay draws relationships between the central assumptions of the two theories and establishes between them what can be called a dialogue.